2010
DOI: 10.1111/j.1442-2050.2009.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

CCL17 and CCL22 chemokines within tumor microenvironment are related to infiltration of regulatory T cells in esophageal squamous cell carcinoma

Abstract: It has been reported that an increased population of regulatory T cells (T-regs) is one of the reasons for impaired anti-tumor immunity. We investigated the frequency of Foxp3(+) T-regs in tumor-infiltrating lymphocytes (TILs) and peripheral blood lymphocytes (PBLs) of patients with esophageal squamous cell carcinoma (ESCC). Furthermore, in order to elucidate the mechanisms behind T-regs accumulation within tumors, we evaluated the relationship between CCL17 or CCL22 expression and the frequency of Foxp3(+) T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
2
44
1
Order By: Relevance
“…These results suggest that the elevated levels of chemokine CCL22 may contribute in the progression of breast cancer. A number of studies have indicated that CCL22 secretion by tumor cells is responsible for intratumoral accumulation of Tregs in ovarian cancer [41], prostate cancer [42], gastric cancer [43], esophageal carcinoma [44], and breast carcinoma [45]. However, it may be concluded that the CCL22 production by tumors cells and/or tumorinfiltrating macrophages induces the intratumoral accumulation of Tregs.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that the elevated levels of chemokine CCL22 may contribute in the progression of breast cancer. A number of studies have indicated that CCL22 secretion by tumor cells is responsible for intratumoral accumulation of Tregs in ovarian cancer [41], prostate cancer [42], gastric cancer [43], esophageal carcinoma [44], and breast carcinoma [45]. However, it may be concluded that the CCL22 production by tumors cells and/or tumorinfiltrating macrophages induces the intratumoral accumulation of Tregs.…”
Section: Discussionmentioning
confidence: 93%
“…Blockade of CCL22 reduced Treg infiltration into ovarian tumours and induced tumour rejection in a murine xenograft model [30]. CCR4 also appears to facilitate Treg tumour infiltration in gastric cancer [35] and oesophageal squamous cell carcinoma [36]. Another chemokine, CCL28, can be expressed by tumour cells during hypoxia, and it is reported to recruit preferentially Tregs expressing CCR10 [37], while in a murine model of pancreatic cancer Tregs have been shown to be recruited to the tumour site via a CCL5/CCR5 axis [38].…”
Section: Mechanisms Driving Regulatory T Cell Accumulation Within Tummentioning
confidence: 97%
“…56,57 Endotoxin administration to pregnant mice did not reduce the production of CCL17 or CCL22; instead, it increased the concentration of these chemokines in the uterine tissues. These data demonstrate that the reduced number of uterine CD41Tregs is not associated with low concentrations of CCL17 and CCL22 in the uterine tissues.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 CCL17 and CCL22 participate in the recruitment of Tregs into the site of inflammation. 56,57 Therefore, we investigated whether the reduction of CD41 Tregs caused by endotoxin administration was due to a diminished production of CCL17 and CCL22 by the uterine tissues. Chemokine concentrations were quantified by ELISAs in uterine protein extracts from pregnant mice injected with PBS or LPS.…”
Section: Lps Administration To Pregnant Mice Causes a Reduction Of Utmentioning
confidence: 99%